Defragmentation of The False-Pseudo Thinking Process of Students in Solving Mathematical Connection Ability Problems: Defragmentasi Proses Berpikir Pseudo Salah Peserta Didik Dalam Menyelesaikan Soal Kemampuan Koneksi Matematis - Lesmana, Belda Nurmultiefa; Supratman, Supratman; Rahayu, Diar Veni (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
The purpose of this research is to describe the defragmentation of pseudo-thinking processes carried out by students in problem solving of mathematical connection abilities. This research uses a descriptive qualitative method. The data collection techniques used mathematical connection ability test with questions on the Pythagorean Theorem which contained indicators of mathematical connecetions (connections between mathematical topics, connections with other disciplines, and connections with everyday life) and unstructured interviews. The research subject were taken from students of class VIII of SMPN 5 Tasikmalaya who experienced a pseudo thingking process that focused on false-pseudo and could take responsibility for the results of their work. The results showed that defragmentation was carried out on students who experienced false-pseudo through several stages, namely scanning, check some errors, repairing (disequilibration, conflict cognitive, and scaffolding), give a chance to re-work, and certain the result. Based on the defragmentation carried out, students who experience false-pseudo can reflect on their mistakes and restructure the thought process that was originally false into correct and clear thought process.